Answer:
14x+10y
Step-by-step explanation:
(2x-5y)(7x-2y)
(2x*7x)(-5y*-2y)
Answer with explanation:
A Rule which expresses that for every input, the output is an even number can be written in many ways
f(x)=2 x , where x is any Integer.
f(n)=4n, where n is any Integer.
f(s)=6s, where s is any Integer.
f(k)=8k, where k is any Integer.
----------------------
There can be many more expressions.
In these expressions,if you replace,x ,n,s and ,k by any integer , the result will be an Even Number(Positive Even Number or Negative Even Number).
B. f(x ) = |x| – 42.67
C. f(x ) = |42.67 – x|
D. f(x ) = 42.67 – |x|
Answer: B
Step-by-step explanation: i got it right on edge
t(4 + 1)
t(5)
5t
What property or properties were used to prove that the expressions are equivalent?
commutative and distributive properties
associative and distributive properties
associative and commutative properties
associative property
The proof used the distributive property and the associative property of multiplication.
Option B is the correct answer.
An expression contains one or more terms with addition, subtraction, multiplication, and division.
We always combine the liketerms in an expression when we simplify.
We also keep all the like terms on one side of the expression if we are dealing with two sides of an expression.
Example:
1 + 3x + 4y = 7 is an expression.com
3 + 4 is an expression.
2 x 4 + 6 x 7 – 9 is an expression.
33 + 77 – 88 is an expression.
We have,
To be specific, the distributiveproperty was used to break down the expression 4t + t as:
4t + t = (4 + 1)t ________(1)
And then the associativeproperty was used to rearrange the terms as:
(4 + 1)t = 5t ________(2)
From (1) and (2)
We have shown that 4t + t is equivalent to 5t.
Thus,
The proof used the distributive property and the associative property of multiplication.
Learn more about expressions here:
#SPJ2
Answer:
its A: commutative and distributive properties
Step-by-step explanation:
i got it right
y=x²-6
are: (Select)
-5) and ( (Select)
-5).
Therefore , the solution of the given problem of equation comes out to be the system of equations' answers are (-1, -5) and (1, -5).
The foundation of a regression model based on linearity is the equation y=mx+b. The inclination is B, and the y-intercept is m. Even though y but also y are separate components, the above line is frequently referred as the "mathematical issues with two variables". Two factors make up bivariate linear equations. There are no simple answers for the applications of linear functions. Y=mx+b .
Here,
We can change the second equation into the first equation to find the solution to the system of equations, which results in:
=> x² + (x²-6) = -4
By condensing and rearrangeing, we obtain:
=> 2x² = 2
=> x² = 1
Consequently, x can either be 1 or -1.
We can determine the appropriate values of y by substituting these values of x into either of the two equations:
When x Equals 1:
=> y = x² - 6 = 1 - 6 = -5
When x Equals -1:
=> y = x² - 6 = 1 - 6 = -5
As a result, the system of equations' answers are (-1, -5) and (1, -5).
To know more about equation visit:
#SPJ1